METHODS OF THERMAL SYSTEM ANALYSIS AND RESULTS OF EXPERIMENTATION OF PHOTOVOLTAIC MODULES BUILT INTO A BUILDING - Nasrullayev, Yusuf (Innovatsion texnologiyalar, 2024)
The use of building-integrated photovoltaic panel systems is treated in the literature taking into account the current state of research in this field. In this article, the entire research work is divided into two different phases. The first stage is the development of a system of photovoltaic modules in a standard state, used in buildings. In the second stage, the characteristics of the experimental installations used to measure the thermal and electrical parameters of photovoltaic panels in the standard state were studied. The main movement of heat, or heat loss, within a building is based on energy efficiency.